Invasion status of hatchery‐origin pink salmon in an unstocked river at the Shiretoko World Natural Heritage Site in northern Japan - Taihei Yamada; Takahiro Nobetsu; Hirokazu Urabe; Futoshi Nakamura (Journal of Fish Biology, 2024)
Hatchery fish and their offspring (including hatchery‐wild hybrids) have lower reproductive success than wild fish. Thus, the straying of hatchery fish may negatively impact wild populations, depending on the number of wild salmon returning and hatchery strays. We investigated the straying status of hatchery‐origin pink salmon ( Oncorhynchus gorbuscha ), which have a higher straying rate than other salmonids, in an unstocked river at the Shiretoko World Natural Heritage Site, Japan. The hatchery strays accounted for 40.0% and 19.0% of the total samples in 2021 and 2022, respectively. These results indicate that hatchery pink salmon have invaded unstocked rivers and potentially genetically affect wild populations.